Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41